WOMEN AS A SUSTAINER IN BUCHI EMECHETA’S THE JOYS OF MOTHERHOOD AND THE BRIDE PRICE - Meflin, Linsheya M; Y.G, Reni (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Black women in general are oppressed and marginalized by their cultural customs and norms that is patriarchy centred. The archetype of woman is framed to accept the woes silently without resistance. This paper analyses the agony of woman as sustainers in various spheres. Eventhough, women get empowered in the society still it is not the same in every community. Igbo women remain as a prey to their culture. Buchi Emecheta, a black womanist writer exposes the woes and heinousness challenged by black women and also it exemplifies the ways to overcome burden and to empower women in their life.